Bioaktivitas Gel Aloe vera pada Gonad Tikus Putih Jantan (Rattus norvegicus) - I Ketut Suardita; I Ketut Puja; Tjok Gde Oka Pemayun (Veterinary Science and Medicine Journal, 2013)
The purpose of this study was to determine Bioactivity of Aloe vera gel on gonad of male white rats (Rattus norvegicus). This research used complately random design, with three treatments namely T0, received placebo as a control; T1, received gel of Aloe vera 300 mg/kg body weight orally; and T2, received gel of Aloe vera 400 mg/kg body weight orally. Aloe vera gel was administrated every day for 21 days. All the treatments repeated three times, and each experimental unit used one white rat. Data found was analyzed using one way of Anova, and the Least Significant Differences (LSD) Test was applied for further analysis. Results showed that Aloe vera gel administration with a dose of 300 mg/kg body weight had effected significantly on the number of spermatogonia cells, live-daed rasio of spermatozoa, and the percentage of sperm abnormality. The result of the research indicates that Aloe vera gel is potentially cytotoxic to testes cells, and so, it’has a high possibilities as an alternative herbal contraceptive agent for animals